2014
DOI: 10.1007/s40145-014-0093-1
|View full text |Cite
|
Sign up to set email alerts
|

Property mapping of polycrystalline diamond coatings over large area

Abstract: Large-area polycrystalline diamond (PCD) coatings are important for fields such as thermal management, optical windows, tribological moving mechanical assemblies, harsh chemical environments, biological sensors, etc. Microwave plasma chemical vapor deposition (MPCVD) is a standard technique to grow high-quality PCD films over large area due to the absence of contact between the reactive species and the filament or the chamber wall. However, the existence of temperature gradients during growth may compromise th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…In our earlier published results [44], it has been shown that how the substrate temperature varies widely across the 100 mm diameter silicon substrate surface, and it was also observed that efficient tuning of the reactor parameters helped in achieving better thermal management for CVD diamond growth. In the present case, citing earlier work report [53], it can be inferred that cubic morphology and abnormality in substrate temperature was responsible for such anomaly in results for as-grown region of study for the sample W3.…”
Section: As-grown Diamond Surface Morphology -Sem Csi Xrdsupporting
confidence: 71%
“…In our earlier published results [44], it has been shown that how the substrate temperature varies widely across the 100 mm diameter silicon substrate surface, and it was also observed that efficient tuning of the reactor parameters helped in achieving better thermal management for CVD diamond growth. In the present case, citing earlier work report [53], it can be inferred that cubic morphology and abnormality in substrate temperature was responsible for such anomaly in results for as-grown region of study for the sample W3.…”
Section: As-grown Diamond Surface Morphology -Sem Csi Xrdsupporting
confidence: 71%
“…The diamond peak positions of both the white and black annealed PCD samples are at 1328.45 cm −1 which is a downshift from the theoretical peak position for single crystal diamond as shown in Figure 6. Down shift of spectra is due to the tensile stress inside the lattice (thermal stress due to expansion mismatch with the Si substrate does not exist as the PCDs are freestanding) [129]. Now on the other hand, a-C (amorphous carbon) hump centre is around 1486 cm −1 for white annealed PCD but such diamond like carbon (DLC) phase centre shifts to 1560 cm −1 for the black annealed PCD sample.…”
Section: Raman Spectroscopymentioning
confidence: 98%
“…Such high energy transmission necessitates large diameter diamond window for efficient thermal management and also low loss transmission [164]. So far large diameter polycrystalline diamond windows [165][166][167] have been used but they have grain boundaries which affect the transmission loss. So the best window material would have been large area single crystal diamond but synthesis of inch size SCD is still a technological challenge.…”
Section: Scd Detectors (Figure 9)mentioning
confidence: 99%